EVALUATION THE EFFICINCY OF SUBSTRATE IN YIELD CHARACTERISTICS AND QUALITIES OF Flammulina velutipes - & et al., Abdulrazzaq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to evaluate the efficiency of the substrate on the productivity and quality for Flammulina velutipes. Results of the effect of different agro-waste sawdust (SD), wheat straw (WS) and palm waste (PW). on the mean fungal mycelium growth shows that Flammulina velutipes gave the highest mean fungal mycelium growth on SD culture media amended with 2, 3, 4% lime at 30c. evaluation the efficiency of the above  agro-waste  substrate morphological and productivity showed that, the shortest period for the full growth of F. velutipes mycelium was on SD substrate, the shortest period for the pinhead formation 8.6days on  the fungus gave highest yield on WS which was 152.3 gm/ bag with 61.1% biological efficiency. The shortest time for full growth of F. velutipes was achieved in PW amended with wheat bran, the highest yield was in WS enriched with wheat bran which 306.7 gm/ bag with 129.3% biological efficiency. Results showed differences in quality characteristics in fruit bodies  of fungi by effect of substrate.